Assessment of soft skills for preservice teachers and its impact on teaching performance in senior secondary schools in North–Central, Nigeria / Macqual Stephen Maren - Macqual Stephen , Maren (2020)
The term soft skill is generating considerable interest in teacher education. Recent developments suggest that in the next few years, soft skills are likely to become a more important teaching component than technical skills. This study was aimed at finding out the level of the implementation of the course “curriculum instruction” in federal universities in Nigeria. Therefore, this study focused on pre-service teacher soft skills gained from participation in the course in other to achieve the ultimate objective of the study. This study used questionnaires and performed data analysis using SmartPLS software in a correlational design with a total of 722 pre-service teachers. Partial least square structural equation modelling (PLS-SEM) results revealed that pre-service teachers gained moderate soft skills from participating in the soft skills course, which, in turn, benefited them in classroom management and, ultimately, teaching success. Further findings indicate that soft skills gained generated a sense in pre-service teachers to have control over their classrooms and has the strongest effect on teaching performance success. These findings shows that pre-service teacher participation in soft skills course generates different kinds of benefits to them at the same time. Turning to findings regarding the effects sizes of the soft skills predictors, results revealed that the effect sizes of some soft skills predictors on soft skills gained were weak, this may mean that not much was done in the implementation of the soft skills curriculum by the institutions to warrant substantive level of soft skills gain by preservice teacher. The analysis did not reveal any significant difference between experienced and novice students in terms of the impact of soft skills on their perception of teaching success. The findings from this study suggest that with substantial soft skills, pre-service teachers need only work into any classroom and then teach successfully upon graduation. This study contributes to theory by discovering new effects sizes for the soft skills predictors as well as the soft skills gained on teaching success. This study also contributes to the curriculum development by developing a curriculum model that can be utilised in the teaching as well as evaluation of soft skills.